Early 'shallow' needle-knife papillotomy and guidewire cannulation: an effective and safe approach to difficult papilla. (May 2015) - Fiocca, Fausto; Fanello, Gianfranco; Cereatti, Fabrizio; Maselli, Roberta; Ceci, Vincenzo; Donatelli, Gianfranco
Introduction: Needle-knife sphincterotomy (NKS), known as 'precut', is used worldwide to facilitate access to the common bile duct when standard cannulation has failed. This procedure is considered hazardous because it is burdened with high procedural related complications (bleeding and perforation). Its right timing is still debated. In this study we report our results using a modified precut approach, early shallow needle-knife papillotomy (eSNKP) coupled with guidewire cannulation in case of difficult papilla. We evaluated its safety and effectiveness. Methods: From 2012 to 2014, 1034 patients underwent therapeutic ERCP. A total of 138 of them presented difficult papilla and were treated with eSNKP performed after 5 failed attempts of standard guidewire cannulation. Deep biliary cannulation rate was recorded, as well as intraoperative and postoperative complication rate. Results: Successful biliary deep cannulation was achieved in 132/138 patients (95.7%) by means of eSNKP. In 6 patients (4.3%), cannulation failed even after eSNKP. ERCP was newly performed 72 hours later with successful and immediate guidewire biliary cannulation. Overall morbidity was 10.1% (14/138). No perforation occurred. Minor bleeding occurred in 4/138 cases (2.9%) and 10/138 patients (7.2%) developed mild pancreatitis. Conclusion: In case of difficult papilla, eSNKP followed by guidewire cannulation increases the successful deep biliary cannulation with low rate of complications.